A Comparative Psycholinguistic Study on the Subjective Feelings of Well-Being Outcomes of Foreign Language Learning in Older Adults From the Czech Republic and Poland - Klimova, Blanka; Pikhart, Marcel; Cierniak-Emerych, Anna; Dziuba, Szymon; Firlej, Krzysztof (Frontiers in Psychology, 2021)
Positive psychology has recently seen the unprecedented rise and has reached vast achievements in the area of quality of life (QoL) improvement. The authors have previously gathered (Klimova & Pikhart 2020) all the available cutting-edge global research into the area of foreign language learning (FLL) in healthy older adults and all the positive consequences it has when taking into account psycholinguistics of older age second language (L2) acquisition. This article attempts to provide the scholars with a pilot study verifying previous findings of positive psychology outcomes from FLL as described in the aforementioned review article. The purpose of this study is to show that there are different aspects of wellbeing that make healthy older people motivated to learn a foreign language at a later age. The research was conducted in the Czech Republic and Poland in two groups of learners aged 55 years and more. The experimental group consisted of 105 Czech respondents who were targeted with an online questionnaire with the aim to determine the level of FLL outcomes connected to QoL in healthy older adults in their L2 acquisition. A control group (n=100) was established of Polish seniors who attended similar language courses. The findings of the research clearly show that FLL has an irreplaceable role as one of several non-pharmacological strategies utilized to improve the aging process and reduce the drawbacks of aging. The results indicate that seniors’ overall satisfaction and subjective feelings of wellbeing are enormously high when attending foreign language classes at an older age. FLL, therefore, creates an environment that can enhance QoL of older adults that can be supplemented by other means such as well-balanced diet, other social activities, sport and physical activity, music, or computer games. All these non-intervention methods can significantly improve the QoL of older adults and the parties engaged and/or responsible for taking care of the older generation should take it into serious consideration.